Discrimination Toward Female Children in Indonesia: Fundamental Causes, Structural Manifestations, and Transformative Initiatives - Farhani Azkia; Nur Arfiyah Febriani; Muhammad Saleh Mude; Badru Tamam (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Discrimination against girls in Indonesia is a multifaceted phenomenon reflecting deeply rooted gender inequalities within the nation's social and patriarchal structures. This research analyzes various dimensions of discrimination experienced by girls, ranging from access to education and healthcare to social participation and protection from gender-based violence. Utilizing a qualitative approach through literature study and secondary data analysis, this research identifies the structural and cultural factors that perpetuate gender injustice. The results indicate that although Indonesia has made significant progress in formal regulations and gender mainstreaming, substantial disparities in the treatment of girls remain, especially in rural areas and communities with strong patriarchal values. Findings highlight that stereotypes, child marriage, and domestic workloads are primary barriers to optimizing girls' potential. The study concludes that a holistic strategy involving legislative harmonization, educational transformation, and multisectoral collaboration is essential for fostering an inclusive environment for girls in Indonesia